Quantum State Transfer with Seamless Frequency‐Connection Through Diamond Optomechanical Cavity. Issue 5 (27th March 2021) - Hao, He; Shan, Lingxiao; Zhang, Qi; Yu, Xiao‐Chong; Gong, Qihuang; Gu, Ying
Abstract: High‐fidelity quantum state transfer, lying in the heart of the scalable quantum network, requires the frequency linkage among different quantum elements. Here, a protocol of quantum state transfer with seamless frequency‐connection between the solid spin and phonon as well as between arbitrary frequency and telecom photons through the diamond optomechanical cavity is proposed. When the diamond optomechanical cavity acts as a quantum node of the network, within each node, the spin state can map to the phonon state with arbitrary frequency via the sideband transition between spins and phonons, and simultaneously such phonon state can convert to photon state without any frequency selection through optomechanical interaction. Furthermore, the communication among quantum nodes is implemented by the evanescent field of nanofiber. The scheme not only enables universal scalable quantum networks for using robust quantum spins, but also offers a paradigm of the building block for optical quantum communications. Abstract : The protocol of quantum state transfer with seamless frequency‐connection is theoretically demonstrated. In the proposed network, the spin state of nitrogen vacancy (NV) center embedded in the optomechanical cavity can be transferred through the nanofiber to the adjacent spin state.